Impact of EUSTAR standardized training on accuracy of modified Rodnan skin score in patients with systemic sclerosis. (5th November 2018) - Park, Jun Won; Ahn, Ga Young; Kim, Ji‐Won; Park, Eun Seong; Kang, Ji‐Hyoun; Chang, Sung Hae; Choi, In Ah; Yoo, Su‐Jin; Park, Jin Kyun; Shin, Kichul; Park, Yong‐Beom; Jun, Jae‐Bum; et al.
Abstract: Objectives: To investigate the impact of European Scleroderma Trials and Research (EUSTAR) standardized training on the accuracy of modified Rodnan skin score (mRSS) in patients with systemic sclerosis (SSc). Methods: Eight SSc patients (four diffuse, four limited) and 10 physicians (4 fellows, 6 professors) were included. Gold‐standard mRSS was performed by a senior instructor. Training comprised a video presentation and a live demonstration. Each physician performed mRSS with no clinical information in all patients: (a) before training; (b) after video session; and (c) after live demonstration. Primary outcome was the change in scoring accuracy, which was defined as the difference from the gold‐standard skin score, as analyzed using a linear mixed model. Results: Mean (standard deviation) difference from the gold‐standard score in all measurements by participants before the training was 7.7 (9.5). Completion of training significantly enhanced mRSS accuracy (adjusted β = −7.61; 95% CI: −11.91 to −3.32). This was largely attributable to the video presentation (adjusted β = −5.47; −9.16 to −1.78), although the live demonstration was associated with numerical reduction in the difference from the gold‐standard score (adjusted β = −2.15; −5.84 to 1.55). Effect of training was prominent in fellows whereas professors showed an increase in the difference from gold‐standard score after training ( P value for interaction <0.001). The intraclass correlation coefficient for physician skin scores was acceptable. However, no significant change was observed after training. Conclusion: New EUSTAR standardized mRSS training significantly enhanced mRSS accuracy, especially in participant with less previous experience in skin scoring.